Actinide and non-actinide production from UO2 fuel in W-SMR: Effects of gadolinium burnable absorber - Uguru, Edwin Humphrey; Sani, Siti Fairus Abdul; Khandaker, Mayeen Uddin; Rabir, Mohamad Hairie (Elsevier Masson, 2020)
Burnable neutron absorbers are used for efficient reactivity control especially in light and heavy water reactors. Effect of gadolinium burnable absorber (GdBA) on reactivity, actinide and non-actinide content of nuclear waste was investigated. Westinghouse small modular reactor (W-SMR) was studied using MCNPX 2.7 code integrated with CINDER90 for the calculations. Positive reactivity swing was observed in fuel assemblies with GdBA rods. The concentration of actinides was relatively higher in FA without GdBA rod compared to those with GdBA rods. The net activity of 241Pu and 239Np were respectively higher compared to other isotopes of plutonium and neptunium and slightly larger in FAs with GdBA rods. However, a significant increase on the concentration of non-actinide inventory was observed which increased with the number of GdBA rods. Therefore, the use of GdBA for reactivity control should be limited to avoid unrealistic reactivity swing and increased non-actinides content of the spent fuel. © 2019 Elsevier Ltd